Neuromonitoring in a Case with Midbrain Cavernoma Operated in Sitting Position: Unveiling the Complexities - Joslita Rebello; Bhoomika Thakore (Journal of Neuroanaesthesiology and Critical Care)
The sitting position is often utilized for mid-brain cavernoma excision due to its several surgical advantages. Intraoperative neuromonitoring aids dynamic functional assessment of neural structures in real-time. In this case report, we discuss the anesthetic management of a patient scheduled for midbrain cavernoma excision in a sitting position. Evoked potential monitoring was performed as the tumor was in proximity to cortico-spinal tracts. We used a combination of inhalational and intravenous anesthetics for the maintenance of anesthesia. Intraoperatively significant events included two episodes of venous air embolism, and loss of motor evoked potentials during the resection of the tumor. These complications were promptly recognized and managed. In the early postoperative period, the patient had motor power 3/5 in flexors of the right upper limb, which improved to normal by Day 5. Thus, good communication among anesthesiologists, neurologists, and surgeons helped identify altered evoked potential signals early, aiding the modification of dissection accordingly.